2014
DOI: 10.1523/jneurosci.5302-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Emission Depletion (STED) Microscopy Reveals Nanoscale Defects in the Developmental Trajectory of Dendritic Spine Morphogenesis in a Mouse Model of Fragile X Syndrome

Abstract: Dendritic spines are basic units of neuronal information processing and their structure is closely reflected in their function. Defects in synaptic development are common in neurodevelopmental disorders, making detailed knowledge of age-dependent changes in spine morphology essential for understanding disease mechanisms. However, little is known about the functionally important finemorphological structures, such as spine necks, due to the limited spatial resolution of conventional light microscopy. Using stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 32 publications
(6 reference statements)
4
47
0
Order By: Relevance
“…97). With the use of stimulated emission depletion microscopy (STED), a normal development of spines with only subtle differences was reported in the Fragile X mouse model (301).…”
Section: A Cognitive Impairmentmentioning
confidence: 99%
“…97). With the use of stimulated emission depletion microscopy (STED), a normal development of spines with only subtle differences was reported in the Fragile X mouse model (301).…”
Section: A Cognitive Impairmentmentioning
confidence: 99%
“…However, to date, few studies have directly quantified excitatory synapse changes in FXS. Moreover, previous studies of dendritic spine density have revealed heterogeneous responses to FMRP loss that are age, cell type, and brain area specific (Cruz-Martín et al, 2012; Galvez and Greenough, 2005; Lauterborn et al, 2013; Nimchinsky et al, 2001; Till et al, 2012; Wijetunge et al, 2014). It is clear, however, that glutamatergic mechanisms that modulate excitatory synapse formation and elimination are affected by FMRP loss (Auerbach et al, 2011; Le Duigou et al, 2011; Gallagher et al, 2004; Huber et al, 2000; Vinueza Veloz et al, 2012; Zhang and Alger, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…actin content in living brain slices using YFP as label [34,35]. Recently, STED microscopy was used to reveal nanoscale morphological alterations in dendritic spines in a mouse model of fragile X syndrome (FXS) [36].…”
Section: Applications Of Sted In Neurobiologymentioning
confidence: 99%